MoS2/graphene composite paper for sodium-ion battery electrodes. - David, Lamuel; Bhandavat, Romil; Singh, Gurpreet (My University, 2014)
We study the synthesis and electrochemical and mechanical performance of layered freestanding papers composed of acid-exfoliated few-layer molybdenum disulfide (MoS₂) and reduced graphene oxide (rGO) flakes for use as a self-standing flexible electrode in sodium-ion batteries. Synthesis was achieved through vacuum filtration of homogeneous dispersions consisting of varying weight percent of acid-treated MoS₂ flakes in GO in DI water, followed by thermal reduction at elevated temperatures. The electrochemical performance of the crumpled composite paper (at 4 mg cm⁻²) was evaluated as counter electrode against pure Na foil in a half-cell configuration. The electrode showed good Na cycling ability with a stable charge capacity of approximately 230 mAh g⁻¹ with respect to total weight of the electrode with Coulombic efficiency reaching approximately 99%. In addition, static uniaxial tensile tests performed on crumpled composite papers showed high average strain to failure reaching approximately 2%.
Keywords: TMDC; Sodium battery; Free-standing electrode; Graphene; MoS2